The Black Heralds in Contact with New York: Historical Context, Translations in English, and Influence on North American Artists - Lomask, Laurie (2020)
Although César Vallejo never traveled to New York in life, the feeling and emotion of his poetry has much in common with what was expressed by North American poets that lived in this city. This paper explores the similarities between The Black Heralds and the poetry produced in and around New York City from the early twentieth century. It also offers a summary of some of the most notable editions in English of The Black Heralds, their reviews, and the influence of Vallejo in North American literary circles today.